4(x+2)²=(2x-3)² alguém me ajuda
Soluções para a tarefa
Respondido por
2
Espero ter ajudado!
pedrohenrique5000:
Muito obrigado!!
Respondido por
0
Resposta:
4(x + 2)² = (2x - 3)²
4(x² + 4x + 4) = 4x² - 12x + 9
4x² + 16x + 16 = 4x² - 12x + 9
4x² - 4x² + 16x + 12x = 9 - 16
0 + 28x = - 7
x = - 7 / 28
x = -7:7 / 28:7
x = - 1 / 4
bons estudos!
Perguntas interessantes
Artes,
10 meses atrás
Matemática,
10 meses atrás
Português,
10 meses atrás
Ed. Técnica,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás